Keanekaragaman dan Kelimpahan Jenis Burung di Kawasan Mangrove Mangunharjo Semarang - Zaida, Amalia; Rahayuningsih, Margareta (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
The Mangunharjo mangrove area is one of the mangrove ecosystems in the coastal area of Semarang City. This study aims to determine the diversity and abundance of bird species, as well as the similarity index of bird communities in the Mangunharjo mangrove area. Data were collected using the point count method in the observation area including ponds, mangroves, rice fields, and beaches. Data collection was carried out periodically from July 2019 to February 2020 with three replications in each area. The results showed that in the Mangunharjo mangrove area there were 66 species of birds from 32 families. The Shannon-Wiener diversity index in the observation area, from the highest to the lowest, were ponds 3.10 (high), mangroves 2.81 (medium), rice fields 2.75 (medium), and beaches 2.66 (moderate). The dominant bird species in the area are the Linci Swallow (15.73%) and the Little Egret (10.61%). While the areas that had the highest Sorensen species similarity index were ponds and mangroves with an index value of 62.5%.